Comparative activity and functional ecology of permafrost soils and lithic niches in a hyper‐arid polar desert. (28th June 2016) - Goordial, Jacqueline; Davila, Alfonso; Greer, Charles W.; Cannam, Rebecca; DiRuggiero, Jocelyne; McKay, Christopher P.; Whyte, Lyle G.
Summary: Permafrost in the high elevation McMurdo Dry Valleys of Antarctica ranks among the driest and coldest on Earth. Permafrost soils appear to be largely inhospitable to active microbial life, but sandstone lithic microhabitats contain a trophically simple but functional cryptoendolithic community. We used metagenomic sequencing and activity assays to examine the functional capacity of permafrost soils and cryptoendolithic communities in University Valley, one of the most extreme regions in the Dry Valleys. We found metagenomic evidence that cryptoendolithic microorganisms are adapted to the harsh environment and capable of metabolic activity at in situ temperatures, possessing a suite of stress response and nutrient cycling genes to fix carbon under the fluctuating conditions that the sandstone rock would experience during the summer months. We additionally identified genes involved in microbial competition and cooperation within the cryptoendolithic habitat. In contrast, permafrost soils have a lower richness of stress response genes, and instead the metagenome is enriched in genes involved with dormancy and sporulation. The permafrost soils also have a large presence of phage genes and genes involved in the recycling of cellular material. Our results underlie two different habitability conditions under extreme cold and dryness: the permafrost soil which is enriched in traits which emphasize survival and dormancy, rather than growth and activity; and the cryptoendolithic environment that selects for organisms capable of growth under extremely oligotrophic, arid and cold conditions. This study represents the first metagenomic interrogation of Antarctic permafrost and polar cryptoendolithic microbial communities.